Compliance of cardiopulmonary resuscitation during in hospital cardiac arrest in a teaching institution - R. Arun Kumar; S. Chandresh; Ahamed Ashar Ali (The Indian Anaesthetists' Forum)
Background: Cardiopulmonary resuscitation (CPR), the essential part of emergency care, is defined as chest compressions and ventilation for survival of cardiac arrest patients, which indicates the influence of outcome and exerts a significant survival benefit after cardiac arrest. Aims: The primary objective of this audit is to determine compliance with the American Heart Association 2020 guidelines by measuring multiple parameters of in hospital CPR quality. Settings and Design: In hospital cardiac arrest (IHCA) patients from all wards of a tertiary care medical college institution was selected for this observational analytic study between January 1, 2019 and December 31, 2021. Materials and Methods: Our study was conducted without randomization, blinding, or control groups, in all code blue victims aged between 20 and 80 years, who suffered cardiac arrest. The results of the compliance of CPR during IHCA in a teaching institution are discussed based on the CPR audit findings under the quality indicators such as protocol deviations, documentation issues, and resource issues. Statistical Analysis: Evaluation, analysis, compilation, and statistical reporting were done on documentation based on these quality indicators. Results and Conclusions: Over a three-year period, 672 cardiac arrest victims analyzed. Of these, 30.91% demonstrated protocol deviation compliance, 15.97% had documentation issues, 12.27% had resource issues, and 40.85% had excellent documentation with no errors or corrections in the critical event monitoring. Out of 672 victims, only 15.62% of cardiac arrest patients achieved spontaneous circulation. The patients who had shockable initial rhythm on the monitor had better outcomes than those who did not have shockable rhythm. Our study revealed that the issues with resuscitation performance in an algorithmic approach were more significant than those with documentation and resource issues. The quality of CPR performance can be improved by demonstrating live and practicing on a mannequin with appropriate teamwork and knowledge sharing.